Kompetensi Kewirausahaan dan Motivasi Kewirausahaan dalam Meningkatkan Kinerja Usaha - Purnamasari, Putri; Mulyadi, Hari; Tarmedi, Eded (Journal of Business Management Education (JBME), 2019)
The purpose of the research is to find out the influence of entrepreneurship competence on business performance, the influence of entrepreneurshp motivation on business performance, and the influence of entrepreneurship competence and entrepreneurshp motivation on business performance. The object becomes the unit of analysis in this research is the Saung Angklung Udjo craftsman. The type of study is using verificative with the method is using an explanatory survey of 30 respondents. The results of this research found that the description of entrepreneurial competence in the high category, the description of entrepreneurial motivation in the strong category, description of business performance in the medium category. Based on the results of this study, it is suggested that entrepreneurial competence be improved, namely the dimensions of competence in managing business that need to be improved and deepened so that the performance of angklung craftsmen increases and can create higher business opportunities. In entrepreneurial motivation, Saung Angklung Udjo craftsmen in Bandung need to be improved in the need for affiliation, where craftsmen must be able to communicate better with coworkers and consumers.